Doublesex mediates species-, sex-, environment- and trait-specific exaggeration of size and shape. Issue 1953 (30th June 2021) - Rohner, Patrick T.; Linz, David M.; Moczek, Armin P.
Abstract : Context-dependent trait exaggeration is a major contributor to phenotypic diversity. However, the genetic modifiers instructing development across multiple contexts remain largely unknown. We use the arthropod tibia, a hotspot for segmental differentiation, as a paradigm to assess the developmental mechanisms underlying the context-dependent structural exaggeration of size and shape through nutritional plasticity, sexual dimorphism and segmental differentiation. Using an RNAseq approach in the sexually dimorphic and male-polyphenic dung beetle Digitonthophagus gazella, we find that only a small portion (3.7%) of all transcripts covary positively in expression level with trait size across contexts. However, RNAi-mediated knockdown of the conserved sex-determination gene doublesex suggests that it functions as a context-dependent master mediator of trait exaggeration in D. gazella as well as the closely related dung beetle Onthophagus taurus . Taken together, our findings suggest (i) that the gene networks associated with trait exaggeration are highly dependent on the precise developmental context, (ii) that doublesex differentially shapes morphological exaggeration depending on developmental contexts and (iii) that this context-specificity of dsx -mediated trait exaggeration may diversify rapidly. This mechanism may contribute to the resolution of conflict arising from environment-dependent antagonistic selection among sexes and divergent developmental contexts in a wide range of animals.